GMAT Question of the Day - Daily to your Mailbox; hard ones only

It is currently 19 Apr 2019, 13:47

Close

GMAT Club Daily Prep

Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track
Your Progress

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.

Close

Request Expert Reply

Confirm Cancel

If x – y = 9, then (x - y/3) - (y - x/3) =

  new topic post reply Question banks Downloads My Bookmarks Reviews Important topics  
Author Message
TAGS:

Hide Tags

 
Math Expert
User avatar
V
Joined: 02 Sep 2009
Posts: 54371
If x – y = 9, then (x - y/3) - (y - x/3) =  [#permalink]

Show Tags

New post 10 Apr 2019, 21:41
00:00
A
B
C
D
E

Difficulty:

  5% (low)

Question Stats:

79% (01:27) correct 21% (01:58) wrong based on 53 sessions

HideShow timer Statistics

CEO
CEO
User avatar
P
Joined: 18 Aug 2017
Posts: 3001
Location: India
Concentration: Sustainability, Marketing
GPA: 4
WE: Marketing (Energy and Utilities)
GMAT ToolKit User Premium Member CAT Tests
If x – y = 9, then (x - y/3) - (y - x/3) =  [#permalink]

Show Tags

New post Updated on: 15 Apr 2019, 07:19
Bunuel wrote:
If x – y = 9, then \((x - \frac{y}{3})(y - \frac{x}{3}) =\)

(A) –4
(B) –3
(C) 0
(D) 12
(E) 27


solve the expression we get
4*(x-y)/3
given x-y= 9
so we get 4*3 = 12
IMO D
_________________
If you liked my solution then please give Kudos. Kudos encourage active discussions.

Originally posted by Archit3110 on 11 Apr 2019, 00:41.
Last edited by Archit3110 on 15 Apr 2019, 07:19, edited 2 times in total.
Manager
Manager
User avatar
B
Joined: 12 Sep 2017
Posts: 214
Re: If x – y = 9, then (x - y/3) - (y - x/3) =  [#permalink]

Show Tags

New post 11 Apr 2019, 17:37
Archit3110

Haha I was trying for 30 minutes and gave up, then I scrolled down and saw your answer, and if you couldn't do it then that it is actually a difficult question xD.

Which was your approach?
Manager
Manager
avatar
G
Joined: 05 Jul 2018
Posts: 104
Location: India
Concentration: General Management, Technology
GRE 1: Q162 V149
GPA: 3.6
WE: Information Technology (Consulting)
Reviews Badge CAT Tests
Re: If x – y = 9, then (x - y/3) - (y - x/3) =  [#permalink]

Show Tags

New post 11 Apr 2019, 21:23
Bunuel wrote:
If x – y = 9, then \((x - \frac{y}{3})(y - \frac{x}{3}) =\)

(A) –4
(B) –3
(C) 0
(D) 12
(E) 27


This is definitely not a 600 level question. Can some expert or Sir Bunuel provide an approach for this.
_________________
Math Expert
User avatar
V
Joined: 02 Sep 2009
Posts: 54371
Re: If x – y = 9, then (x - y/3) - (y - x/3) =  [#permalink]

Show Tags

New post 11 Apr 2019, 21:29
SVP
SVP
User avatar
V
Status: It's near - I can see.
Joined: 13 Apr 2013
Posts: 1595
Location: India
Concentration: International Business, Operations
Schools: INSEAD Jan '19
GPA: 3.01
WE: Engineering (Real Estate)
Reviews Badge
Re: If x – y = 9, then (x - y/3) - (y - x/3) =  [#permalink]

Show Tags

New post 11 Apr 2019, 21:55
1
Bunuel wrote:
If x – y = 9, then \((x - \frac{y}{3}) - (y - \frac{x}{3}) =\)

(A) –4
(B) –3
(C) 0
(D) 12
(E) 27


\((x - \frac{y}{3}) - (y - \frac{x}{3}) =\)

\(\frac{{3x - y - 3y + x}}{3}\)

\(\frac{{4x - 4y}}{3}\)

\(\frac{{4(x - y)}}{3}\)

\(\frac{4 * 9}{3}\)

\(12\) (D)
_________________
"Do not watch clock; Do what it does. KEEP GOING."
Intern
Intern
avatar
B
Joined: 16 Jan 2019
Posts: 18
Re: If x – y = 9, then (x - y/3) - (y - x/3) =  [#permalink]

Show Tags

New post 11 Apr 2019, 23:33
The equation can be simply rearranged as (x-y) + (x-y)*1/3

Substituting for x-y we get 12

(D)

Posted from my mobile device
Manager
Manager
avatar
S
Joined: 24 Nov 2018
Posts: 106
Location: India
GPA: 3.27
WE: General Management (Retail Banking)
Premium Member CAT Tests
Re: If x – y = 9, then (x - y/3) - (y - x/3) =  [#permalink]

Show Tags

New post 12 Apr 2019, 13:59
Bunuel wrote:
If x – y = 9, then \((x - \frac{y}{3}) - (y - \frac{x}{3}) =\)

(A) –4
(B) –3
(C) 0
(D) 12
(E) 27


\((x-\frac{y}{3})-(y-\frac{x}{3})=\frac{4x}{3}-\frac{4y}{3}=\frac{4*(x-y)}{3}=\frac{4*9}{3}=12\)

IMO, option D>
_________________
Kudos encourage discussions. Share it to amplify collective education!
Manager
Manager
User avatar
G
Joined: 21 Feb 2019
Posts: 103
Location: Italy
Premium Member CAT Tests
If x – y = 9, then (x - y/3) - (y - x/3) =  [#permalink]

Show Tags

New post 13 Apr 2019, 02:09
Fastest way:

\((x - \frac{y}{3}) - (y - \frac{x}{3}) = (x - y) + \frac{1}{3}(x - y) = 9 + 3 = 12\).
_________________
If you like my post, Kudos are appreciated! Thank you.


MEMENTO AUDERE SEMPER
Director
Director
User avatar
D
Joined: 27 May 2012
Posts: 730
Re: If x – y = 9, then (x - y/3) - (y - x/3) =  [#permalink]

Show Tags

New post 15 Apr 2019, 03:15
Archit3110 wrote:
Bunuel wrote:
If x – y = 9, then \((x - \frac{y}{3})(y - \frac{x}{3}) =\)

(A) –4
(B) –3
(C) 0
(D) 12
(E) 27


solve the expression we get
4*(x-y)/3
given x-y= 3
so we get 4*3 = 12
IMO D


Just a small correction required here x-y =9.
_________________
- Stne
CEO
CEO
User avatar
P
Joined: 18 Aug 2017
Posts: 3001
Location: India
Concentration: Sustainability, Marketing
GPA: 4
WE: Marketing (Energy and Utilities)
GMAT ToolKit User Premium Member CAT Tests
Re: If x – y = 9, then (x - y/3) - (y - x/3) =  [#permalink]

Show Tags

New post 15 Apr 2019, 07:19
stne ; edited thanks :)
_________________
If you liked my solution then please give Kudos. Kudos encourage active discussions.
Target Test Prep Representative
User avatar
P
Status: Founder & CEO
Affiliations: Target Test Prep
Joined: 14 Oct 2015
Posts: 5800
Location: United States (CA)
Re: If x – y = 9, then (x - y/3) - (y - x/3) =  [#permalink]

Show Tags

New post 16 Apr 2019, 17:42
Bunuel wrote:
If x – y = 9, then \((x - \frac{y}{3}) - (y - \frac{x}{3}) =\)

(A) –4
(B) –3
(C) 0
(D) 12
(E) 27


Simplifying, we have:

3x/3 - y/3 - 3y/3 + x/3

(4x - 4y)/3

4(x - y)/3

Since x - y = 9, we have 4(9)/3 = 12.

Answer: D
_________________

Scott Woodbury-Stewart

Founder and CEO

Scott@TargetTestPrep.com
TTP - Target Test Prep Logo
122 Reviews

5-star rated online GMAT quant
self study course

See why Target Test Prep is the top rated GMAT quant course on GMAT Club. Read Our Reviews

GMAT Club Bot
Re: If x – y = 9, then (x - y/3) - (y - x/3) =   [#permalink] 16 Apr 2019, 17:42
Display posts from previous: Sort by

If x – y = 9, then (x - y/3) - (y - x/3) =

  new topic post reply Question banks Downloads My Bookmarks Reviews Important topics  


Copyright

GMAT Club MBA Forum Home| About| Terms and Conditions and Privacy Policy| GMAT Club Rules| Contact| Sitemap

Powered by phpBB © phpBB Group | Emoji artwork provided by EmojiOne

Kindly note that the GMAT® test is a registered trademark of the Graduate Management Admission Council®, and this site has neither been reviewed nor endorsed by GMAC®.